Undergraduates’ Attitude toward Language in a Nigeria University - Alao, Pascal Adebayo (NIU Journal of Humanities, 2020)
This study investigated the attitude of some graduating students of French language in a Nigerian University using Olabisi Onabanjo University. Ago-Iwoye as an example. A total of forty-seven (47) students from penultimate (300level) and final year (400level) undergraduates from two faculties. Arts and Education were administered a structured questionnaire. These groups were chosen because they have undergone the mandatory. French language immersion programme in the Nigerian French language Village. Data collected were analysed with simple percentage and t-test statistics in SPSS statistical programme. The results revealed that students have positive attitudes towards learning the language. It also revealed that there is a significant difference, according to gender, academic levels and age in undergraduates’ attitudes towards the study of French language. Keywords : Attitude, graduating students, French, Nigerian Universities.